Molecular epidemiology of carbapenem-resistant Klebsiella pneumoniae ST15-KL19 isolates from ICU patients in a Chinese tertiary hospital - Xie, Qiang; Xu, Tiantian; Chen, Ling; Shi, Chunhong (Frontiers in Microbiology, 2025)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) represents a growing threat in healthcare settings, with sequence type 15 (ST15) increasingly recognized as a high-risk lineage. To characterize its molecular and epidemiological features in eastern China, we investigated 17 non-duplicate ST15 CRKP isolates obtained from patients in the intensive care unit (ICU) of a tertiary hospital in Chuzhou. Whole-genome sequencing, antimicrobial susceptibility testing, resistance and virulence gene profiling, plasmid analysis, and core genome multilocus sequence typing with SNP analysis were performed. All isolates belonged to the ST15-KL19 clone and carried a conserved set of resistance genes, including aminoglycoside-modifying enzymes (aac(3)-IId, aac(6′)-Ib-cr), extended-spectrum β-lactamases (blaCTX-M-15, blaSHV-106, blaTEM-1B), carbapenemase (blaKPC-2), oxacillinase (blaOXA-1), and additional determinants such as fosA, oqxA, and oqxB. The isolates exhibited complete resistance to β-lactams and carbapenems but remained susceptible to tigecycline and amikacin. Two predominant virulence gene patterns were identified, with most isolates harboring fimbrial operons, siderophore systems, and T6SS components. Plasmid analysis revealed the presence of IncFIB(K) and repB(R1701). Phylogenetic analysis demonstrated three clusters with strong spatiotemporal overlap, supporting nosocomial transmission. Clinically, infections were associated with prolonged ICU stays and poor outcomes, with only 17.6% of patients achieving full recovery and 5.9% experiencing in-hospital mortality. These findings indicate that ST15-KL19 CRKP constitutes a regionally endemic clone with high resistance and virulence potential, underscoring the urgent need for strengthened molecular surveillance and stringent infection control measures.